Morphological symmetry of the radius and ulna-Can contralateral forearm bones utilize as a reliable template for the opposite side? - Eunah Hong (Public Library of Science (PLoS), 2021)
The most important precondition for correction of the affected forearm using data from the contralateral side is that the left and right bone features must be similar, in order to develop patient-specific instruments (PSIs) and/or utilize computer-assisted orthopedic surgery (CAOS). The forearm has complex anatomical structure, and most people use their dominant hand more than their less dominant hand, sometimes resulting in asymmetry of the upper limbs. The aim of this study is to investigate differences of the bilateral forearm bones through a quantitative comparison of whole bone parameters including length, volume, bowing, and twisting parameters, and regional shape differences of the forearm bones. In total, 132 bilateral 3D radii and ulnae 3D models were obtained from CT images, whole bone parameters and regional shape were analyzed. Statistically significant differences in whole bone parameters were not shown. Regionally, the radius shows asymmetry in the upper section of the central part to the upper section of the distal part. The ulna shows asymmetry in the lower section of the proximal part to the lower section of the central part. Utilizing contralateral side forearm bones to correct the affected side may be feasible despite regional differences in the forearm bones of around 0.5 mm.